2020
DOI: 10.1016/j.wem.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Accidents Related to Snakebites in the Amazon—Two Case Reports

Abstract: The objective of this case series was to describe 2 patients presenting with subarachnoid hemorrhage with hydrocephalus and hemoventricle after a snakebite caused by presumed Bothrops ssp. Both cases occurred in the municipality of Guajar a (Amazonas state), Western Brazilian Amazon. Both cases featured delay in administration of serum therapy, which may have contributed to the emergence of complications such as stroke. Patient 1 was admitted to hospital 16 h after the snakebite occurred. Before receiving anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Conversely, the venom is diluted into a much larger blood volume in human bite victims, which typically does not result in stroke, although this has been noted on occasion (145,146). Instead, when venom is diluted throughout a large blood volume, venom-induced consumption coagulopathy (VICC) occurs via depletion of clotting factors following excessive activity of the coagulation cascade (147,148).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the venom is diluted into a much larger blood volume in human bite victims, which typically does not result in stroke, although this has been noted on occasion (145,146). Instead, when venom is diluted throughout a large blood volume, venom-induced consumption coagulopathy (VICC) occurs via depletion of clotting factors following excessive activity of the coagulation cascade (147,148).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the prevalence of cerebrovascular complications in Bothrops envenoming, it was found that 2.6% of the victims developed a cerebrovascular event, of which about 60% died and 40% remained with sequelae [40]. Delay in antivenom administration may contribute to the onset of such complications [16,38,41]. Systemic bleeding is significantly associated with higher snakebite fatality [5] and amputation [42].…”
Section: Systemic Hemorrhagementioning
confidence: 99%
“…In Brazil, medically important snakes belong to two families, with emphasis on genus Bothrops , Crotalus , and Lachesis belonging to family Viperidae, and Micrurus under family Elapidae 15 . At the national level, approximately 90% of snakebites are caused by the genus Bothrops 12 , whose venom cause severe local symptoms such as edema, ecchymosis, and necrosis, as well as systemic symptoms such as cerebrovascular accident (CVA) and acute kidney injury (AKI) 16 , 17 . The genus Crotalus ranks second in the number of snakebites, accounting for approximately 8% of the cases 12 .…”
Section: Introductionmentioning
confidence: 99%